2021
DOI: 10.1177/13621688211052793
|View full text |Cite
|
Sign up to set email alerts
|

The relative effectiveness of immediate and delayed corrective feedback in video-based computer-mediated communication

Abstract: This study investigated the relative effectiveness of immediate and delayed corrective feedback on the acquisition of -ing/ -ed participial adjectives by Spanish English-as-a-foreign-language learners in video-based computer-mediated communication. Fifty-two participants took part in a communicative task in one of four groups (two experimental and two control). The immediate-feedback group received explicit corrective feedback during the task whereas the delayed-feedback group received the feedback 24 hours la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…As most previous studies have been conducted in face-to-face or text-based SCMC conditions, the current study extends the existing body of research by showing that CF provided in videobased SCMC may also be beneficial for L2 acquisition. This result is consistent with the findings of a small number of prior studies that also reported positive results for CF in videobased SCMC (Canals et al, 2021;Monteiro, 2014;Rassaei, 2017). The finding that learners in the treatment groups made significant gains over time suggests that CF was effective in drawing their attention to the target form and contributed to the development of their internal L2 system (Abbuhl, 2021;Gass, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As most previous studies have been conducted in face-to-face or text-based SCMC conditions, the current study extends the existing body of research by showing that CF provided in videobased SCMC may also be beneficial for L2 acquisition. This result is consistent with the findings of a small number of prior studies that also reported positive results for CF in videobased SCMC (Canals et al, 2021;Monteiro, 2014;Rassaei, 2017). The finding that learners in the treatment groups made significant gains over time suggests that CF was effective in drawing their attention to the target form and contributed to the development of their internal L2 system (Abbuhl, 2021;Gass, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…However, in a study focusing on vocabulary learning, Yanguas (2012) reported that the group that received CF during video chat failed to maintain their gains on a production task over time. In two recent studies, Rassaei (2017) and Canals et al (2021) reported positive results for CF provided during video chat, but since neither study included a delayed posttest, it was unclear whether true learning had taken place. Thus, it seems that existing studies have not provided conclusive results regarding the effectiveness of CF in video-based SCMC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been argued that the explicitness of the feedback was especially helpful for learners to confirm or refute interlanguage hypotheses, given that several studies have shown an advantage for explicit feedback, especially in CALL (e.g., Rosa and Leow, 2004). Likewise, those studies that applied more explicit types of feedback in other modalities also tend to find no difference between the two feedback conditions (Varnosfadrani, 2006;Canals et al, 2021). For instance, Canals et al (2021) investigated the relative effectiveness of immediate and delayed CF in video-based CMC and argued the feedback type used in the study, i.e., explicit corrections, might have contributed to no statistical differences between the two feedback timing conditions.…”
Section: The Explicitness Of the Feedbackmentioning
confidence: 98%
“…Likewise, those studies that applied more explicit types of feedback in other modalities also tend to find no difference between the two feedback conditions (Varnosfadrani, 2006;Canals et al, 2021). For instance, Canals et al (2021) investigated the relative effectiveness of immediate and delayed CF in video-based CMC and argued the feedback type used in the study, i.e., explicit corrections, might have contributed to no statistical differences between the two feedback timing conditions. Because explicit corrections are relatively direct about the ungrammaticality of the learner's utterance, they might have promoted the mental comparison between the error and correct alternative more reliably.…”
Section: The Explicitness Of the Feedbackmentioning
confidence: 98%
See 1 more Smart Citation